Long-term pharmacokinetics of an extract of isoflavones from red clover (Trifolium pratense) - Howes, Jan; Waring, Mark; Huang, Li; Howes, Laurence G (The journal of alternative and complementary medicine (New York, N.Y.), 2002)
To study the pharmacokinetics of isoflavones from red clover (Trifolium pratense) after long-term administration as a once-daily dietary supplementary. Fourteen (14) subjects who had been consuming a low-isoflavone diet for 2 weeks were given an oral dose of two isoflavone tablets (approximately 80 mg of total isoflavones) daily for 2 weeks and appeared for a study day at 9:00 AM after an overnight fast on the day that they were to receive the last dose. Plasma samples were collected for a 48-hour period after the last dose. Plasma isoflavones were assayed by high-performance liquid chromatography (HPLC). Trough plasma levels were significantly higher for daidzein and genistein after long-term dosing than levels taken prior to the commencement of the study and plasma levels of isoflavones after long-term dosing were in the range previously reported in populations that consume an isoflavone-rich diet. The plasma half-lives observed after long-term administration were, in most cases, consistent with once-daily administration. Isoflavones have pharmacokinetic characteristics that suggest that once-daily administration is adequate when they are administered long-term as dietary supplements.